ChemInform Abstract: Chemoselective Chromium(II)‐Catalyzed Cross‐Coupling Reactions of Dichlorinated Heteroaromatics with Functionalized Aryl Grignard Reagents. Issue 25 (5th June 2015) - Steib, Andreas K.; Kuzmina, Olesya M.; Fernandez, Sarah; Malhotra, Sushant; Knochel, Paul
Abstract: The regioselective α‐arylation of α‐chloropyridines and quinoline is catalyzed by CrCl2 .